L’identité argentine ou la construction d’un mythe littéraire entre Europe et Amérique - Lionel Souquet (Amnis)
This paper focuses on some of the archetypes which have contributed to the construction of the rather theatrical and blurred picture of the Argentinian – including in Europe. Paradoxically enough, this literary image is not so far removed from the socio-cultural reality as the identity of the Latin-American novelist is often defined by his or her engagement with reality through (philosophical, political, historical and sociological) description and analysis. A study of the portrayal by 19th intellectuals of the gaucho – a figure known for his emblematic strength but also the victim of all manner of ideological manipulations – shows how Argentinian identity was constructed around a Civilization / Barbarity opposition, traces of which can still be found today. The paper then focuses on immigration, a key factor in the changes within Argentinian society and its inclusion in the 20th century. This is followed by a study of the portrayal of the middle class (which differentiates the country from the rest of Latin America) as seen through Manuel Puig’s idiosyncratic descriptions. By ‘imaging’ a nation, literature shapes ‘reality’ but, then, literature with all its manipulations of reality is also part of that reality.